Kondisi Kamar Hunian, Sanitasi Dasar, dan Keluhan Kesehatan di Asrama Mahasiswa - Ismiati, Ayu Tri; Wijayanti, Yuni (Indonesian Journal of Public Health and Nutrition, 2021)
ABSTRACT Background: The dormitory is a residence for students who have a high potential for health and environmental problems, one of which is the student dormitory of Universitas Negeri Semarang. Based on the results of the preliminary study, the physical condition of the living room and basic sanitation in the dormitory was in poor condition accompanied by health complaints experienced by students. The purpose of this study was to describe the condition of the residential room, basic sanitation, and health complaints in the UNNES student dormitory in 2020. Methods: This type of research used a quantitative descriptive method with a cross-sectional approach with the research subjects being male and female student dormitories at Universitas Negeri Semarang. The variables in the study include ceiling conditions, wall conditions, floor conditions, room temperature, humidity, lighting intensity, ventilation conditions, occupancy room density, clean water supply, garbage disposal, feces disposal, wastewater disposal, and health complaints. Sampling using a proportional random sampling technique. Data were analyzed using univariate analysis. Results: The results showed that the room conditions met the criteria, namely 95.1% ceiling, 100% walls, 96.7% floor, 52.8% temperature, 74.8% humidity, 91.9% lighting intensity, and 100% ventilation. Basic sanitation that meets the criteria is only the provision of clean water. While the variable of health complaints, there were 95.2% of people experiencing complaints on the skin, 78.4% experiencing complaints on breathing, and 37.3% experiencing complaints on digestion. Conclusion: The conclusion of this study is a description of the condition of the living room, basic sanitation, and health complaints in the student dormitories of Universitas Negeri Semarang. There are still variables that do not meet the criteria when compared with health regulations. ABSTRAK Latar Belakang: Asrama merupakan tempat tinggal bagi mahasiswa yang berpotensi tinggi mengalami masalah kesehatan dan lingkungan, salah satunya adalah asrama mahasiswa Universitas Negeri Semarang. Berdasarkan hasil studi pendahuluan, kondisi fisik kamar hunian dan sanitasi dasar di asrama dalam keadaan kurang baik disertai adanya keluhan kesehatan yang dialami mahasiswa. Tujuan penelitian ini untuk mengetahui gambaran kondisi kamar hunian, sanitasi dasar, dan keluhan kesehatan di asrama mahasiswa UNNES tahun 2020. Metode: Jenis penelitian menggunakan metode deskriptif kuantitatif dengan pendekatan cross sectional dengan subjek penelitian adalah asrama mahasiswa putra dan putri Universitas Negeri Semarang. Variabel dalam penelitian meliputi kondisi langit-langit, kondisi dinding, kondisi lantai, suhu kamar hunian, kelembaban kamar hunian, internsitas pencahayaan, kondisi ventilasi, kepadatan kamar hunian, penyediaan air bersih, pembuangan sampah, pembuangan tinja, pembuangan air limbah, dan keluhan kesehatan. Pengambilan sampel menggunakan teknik proportional random sampling. Data dianalisis dengan menggunakan analisis univariat. Hasil: Hasil penelitian menunjukkan kondisi kamar hunian yang memenuhi kriteria yaitu langit-langit 95,1%, dinding 100%, lantai 96,7%, suhu 52,8%, kelembaban 74,8%, intensitas pencahayaan 91,9%, dan ventilasi 100%. Sanitasi dasar yang memenuhi kriteria hanya penyediaan air bersih. Sedangkan variabel keluhan kesehatan terdapat 95,2% orang mengalami keluhan pada kulit, 78,4% mengalami keluhan pada pernapasan, dan 37,3% mengalami keluhan pada pencernaan. Kesimpulan: Kesimpulan dalam penelitian ini adalah gambaran kondisi kamar hunian, sanitasi dasar, dan keluhan kesehatan di asrama mahasiswa Universitas Negeri Semarang masih terdapat variabel yang tidak memenuhi kriteria jika dibandingkan dengani peraturan kesehatan.